Ex ante appraisal of agricultural research and extension: a choice experiment on climbing beans in Burundi - Lambrecht, Isabel B.; Vranken, L.; Merckx, Roel; Vanlauwe, Bernard; Maertens, M. (SAGE Publications, 2015)
Research on agricultural technology adoption generally occurs ex post, after the introduction of a technology. In this paper, the authors use a choice experiment to reveal farmers’ preferences for new agricultural technologies ex ante, before new technologies are developed and introduced. The authors implement a choice experiment among 200 farmers in Burundi and use mixed logit models to analyse preferences for specific traits of improved climbing bean varieties. It was found that farmers had a strong preference for climbing bean varieties that resulted in higher yields and improved soil fertility, while the maturation period and the responsiveness to fertilizer were less important. Seed price was found to matter only for the most food-insecure farmers. These choice experimental results can inform agricultural research and extension programmes ex ante to take into account farmers’ preferences and accelerate the adoption of new technologies.Research on agricultural technology adoption generally occurs ex post, after the introduction of a technology. In this paper, the authors use a choice experiment to reveal farmers’ preferences for new agricultural technologies ex ante, before new technologies are developed and introduced. The authors implement a choice experiment among 200 farmers in Burundi and use mixed logit models to analyse preferences for specific traits of improved climbing bean varieties. It was found that farmers had a strong preference for climbing bean varieties that resulted in higher yields and improved soil fertility, while the maturation period and the responsiveness to fertilizer were less important. Seed price was found to matter only for the most food-insecure farmers. These choice experimental results can inform agricultural research and extension programmes ex ante to take into account farmers’ preferences and accelerate the adoption of new technologies.Research on agricultural technology adoption generally occurs ex post, after the introduction of a technology. In this paper, the authors use a choice experiment to reveal farmers’ preferences for new agricultural technologies ex ante, before new technologies are developed and introduced. The authors implement a choice experiment among 200 farmers in Burundi and use mixed logit models to analyse preferences for specific traits of improved climbing bean varieties. It was found that farmers had a strong preference for climbing bean varieties that resulted in higher yields and improved soil fertility, while the maturation period and the responsiveness to fertilizer were less important. Seed price was found to matter only for the most food-insecure farmers. These choice experimental results can inform agricultural research and extension programmes ex ante to take into account farmers’ preferences and accelerate the adoption of new technologies.Research on agricultural technology adoption generally occurs ex post, after the introduction of a technology. In this paper, the authors use a choice experiment to reveal farmers’ preferences for new agricultural technologies ex ante, before new technologies are developed and introduced. The authors implement a choice experiment among 200 farmers in Burundi and use mixed logit models to analyse preferences for specific traits of improved climbing bean varieties. It was found that farmers had a strong preference for climbing bean varieties that resulted in higher yields and improved soil fertility, while the maturation period and the responsiveness to fertilizer were less important. Seed price was found to matter only for the most food-insecure farmers. These choice experimental results can inform agricultural research and extension programmes ex ante to take into account farmers’ preferences and accelerate the adoption of new technologies.